2012
DOI: 10.1186/1756-9966-31-64
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a recombinant eukaryotic expression vector containing PHD3 gene and its expression in HepG2 cells

Abstract: Prolyl hydroxylase domain 3 (PHD3) is a hypoxia inducible factor-α (HIFα) regulator; it degrades HIFα in the presence of oxygen. Recently, there have been an increasing number of studies about the role of PHD3 in proliferation and apoptosis of cancer cells. However, most of the evidence for the role of PHD3 is observational, and little is known of the molecular mechanism. In our current study, we constructed a recombinant eukaryotic expression vector containing the PHD3 gene and detected its biological activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The present study aimed to explore the association between PHD3 and HIF2α expression in HCC (under hypoxic conditions). Several studies have demonstrated that PHD3 serves a novel role in the progression and prognosis of cancer (15-24); PHD3 is also able to induce apoptosis and inhibit proliferation in cancer cells (22)(23)(24)(25)(26)(27)(28)(29). To the best of our knowledge, the present study is the first to report that PHD3 overexpression induces apoptosis and inhibits growth and proliferation in HCC cells.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The present study aimed to explore the association between PHD3 and HIF2α expression in HCC (under hypoxic conditions). Several studies have demonstrated that PHD3 serves a novel role in the progression and prognosis of cancer (15-24); PHD3 is also able to induce apoptosis and inhibit proliferation in cancer cells (22)(23)(24)(25)(26)(27)(28)(29). To the best of our knowledge, the present study is the first to report that PHD3 overexpression induces apoptosis and inhibits growth and proliferation in HCC cells.…”
Section: Introductionmentioning
confidence: 59%
“…Given the increasing number of observational studies on PHD3, considerable attention has been focused on the mechanism of PHD3 (17,18,(24)(25)(26)(27)(28). Su et al (18) revealed that PHD3-induced apoptosis is dependent on nerve growth factor by activating caspase-3 in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another two studies provided further information of human hepatoma cell line. By using PHD3 steady expression plasmid transfected HepG2 and constructing HepG2-bearing subcutaneous tumor in nude mice, researchers found out that PHD3 gene may inhibit proliferation and induce apoptosis by activating caspase-3 activity [ 63 , 64 ]. Taken together, the tumor suppressive effect of FIH and PHD3 should exert through inhibiting proliferation or blocking neovascularization.…”
Section: Discussionmentioning
confidence: 99%